2004
DOI: 10.1016/j.bbmt.2003.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Which donor should be chosen for hematopoietic stem cell transplantation among unrelated HLA-A, -B, and -DRB1 genomically identical volunteers?

Abstract: The aim of this study was to identify significant prognostic factors by using unrelated genomically HLA-A, -B and -DRB1-identical donors. Such data could help to choose the best donor. We studied 136 consecutive patients with hematologic malignancies and a median age of 32 years (range, 0-55 years) who received hematopoietic stem cell transplantation. Bone marrow grafts were given to 83 and peripheral blood stem cells to 53 patients. The cumulative incidence of grade II to IV acute graft-versus-host disease (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
5
26
1
Order By: Relevance
“…30 In another study, multivariate analysis showed that poor leukaemia-free survival is associated with CMV-seronegative grafts to CMV-seropositive recipients. 27 These results were not confirmed by a recent study that detected no adverse effects of donor and recipient CMV serology status on survival, GvHD, engraftment or relapse. 31 The preemptive use of drugs such as ganciclovir and CMV-specific T cells might contribute to preventing CMV infections in recipients who are at risk.…”
Section: Disease Phasementioning
confidence: 76%
See 2 more Smart Citations
“…30 In another study, multivariate analysis showed that poor leukaemia-free survival is associated with CMV-seronegative grafts to CMV-seropositive recipients. 27 These results were not confirmed by a recent study that detected no adverse effects of donor and recipient CMV serology status on survival, GvHD, engraftment or relapse. 31 The preemptive use of drugs such as ganciclovir and CMV-specific T cells might contribute to preventing CMV infections in recipients who are at risk.…”
Section: Disease Phasementioning
confidence: 76%
“…Conflicting results have been reported on the relative importance of various class I and II loci mismatches on outcome. [21][22][23][24][25][26][27][28] Early studies reported that low-resolution mismatches at HLA-A and -B Ags, and high-resolution mismatches at HLA-DRB1 allele are associated with worse GvHD and survival. [21][22] Matching algorithms favoured class II matching over class I matching when a complete match could not be found.…”
Section: Matching Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…14 HLA typing for class I and class II was carried out by allele-level PCR amplification with sequence-specific primers. 5 Of the 27 UCB cases, 1 patient had an HLA-A, -B and -DRb1-matched donor, 1 got a two minor Ag-mismatched graft, 14 had one HLA-Ag mismatch (8 patients, in addition, had minor mismatches) and 12 had two HLA Ag mismatches out of which 6 in addition had minor mismatches ( Table 1). The MM URD grafts included one HLA-A mismatch in six patients, an HLA-B Ag mismatch in five, and a DRb1 Ag mismatch in three patients.…”
Section: Donors and Tissue Typingmentioning
confidence: 99%
“…1,2 With improved genomic tissue typing, results using unrelated donors are very similar to those obtained using HLA-identical siblings. [3][4][5] Despite the fact that the volunteer registries now contain more than 12 million unrelated donors, the pool is not large enough to find an HLA-matched donor for all patients. Especially for those with rare HLA alleles, an alternative donor must be sought.…”
Section: Introductionmentioning
confidence: 99%